Meretas Kembali Pemikiran Muhammad Natsir (Praktek Pendidikan Integral, Harmonis Dan Universal) - Durhan Durhan (LPPM Institut Agama Islam Al-Hikmah Tuban, 2018)
Abstract: The concept offered by Muhammad Natsir is an integral, humanist and universal educational concept. Natsir strongly opposed the practice of dichotomy in education. For him, education in education will cause a lack of knowledge about the students. The first knowledge that must be taught to students is the science of Tawheed. This knowledge is very important, considering the introduction of students to servants must be introduced during childhood. By itself, when children are familiar with their Lord, they will easily run what they are told and know what is forbidden. The second material that must be introduced to students is language material. With this material, students will be trained in procedures that speak polite and flexible language. In addition, education will be considered advanced, if the education has a quality teacher, professional and authoritative. So, it takes a variety of ways to polish the teacher to become a teacher who is truly a teacher. This concept of Muhammad Natsir may be able to answer various problems experienced by the world of education today, considering that education today often occurs unwanted problems occur.